Characterization of intra‐ply shear behaviors of unidirectional prepregs during hot diaphragm forming process. Issue 2 (23rd November 2020) - Zhao, Yueqing; Gu, Yizhuo; Zhang, Tao; Li, Hongfu; Zhang, Boming; Zhang, Zhenchong
Abstract: Intra‐ply shear is the most important deformation mode in composite sheet forming. In this study, the intra‐ply shear behaviors of cross‐ply unidirectional carbon fiber/epoxy prepregs under double diaphragm compaction at different temperatures and cross‐head rates were investigated by a home‐made testing system. The experimental test results indicate that uniform temperature distribution and low forming speed in double diaphragm process help to obtain high‐quality products. A modified model based on the temperature, cross‐head rate and the level of compaction was proposed for shear angle prediction. Then fifth‐degree polynomial and power functions combined with two rate‐independent theories were used to calculate the shear force and modulus. The shear force and shear modulus are strongly influenced by the function that describing the relationship between the shear force and shear angle.